Holocene Paleosecular Variations Recorded by Relict Magnetic Minerals in the Anoxic Black Sea Sediments. Issue 5 (14th May 2022) - Liu, Jiabo; Nowaczyk, Norbert R.; Jiang, Xiaodong; Zhong, Yi; Wirth, Richard; Liu, Qingsong; Arz, Helge W.
Abstract: Continuous paleosecular variations reconstructed from sedimentary archives have remarkably deepened our insights into the dynamics of the Earth's magnetic field as well as the chronological purpose. Nevertheless, to construct reliable sedimentary paleomagnetic records in diagenetic reducing sediments is challenging generally due to the pervasive magnetic mineral diagenesis. The relict magnetic minerals are residuals after diagenesis and probably able to record a depositional remanent magnetization, thus it is worthy to explore their paleomagnetic potentials. For this study, two Black Sea sediment cores covering the past 8 ka were subjected to mineralogical and paleo‐ and rock magnetic analyses. Paramagnetic pyrite framboids are pervasive in the studied sediments deposited under anoxic bottom water conditions in the Black Sea. In addition, relict magnetic minerals of ferrous hemoilmenite, Fe‐Mn and Fe‐Cr spinels, and magnetite inclusions are also present in the studied cores. Compared to the previous published paleomagnetic results from the same cores over the last glacial period (20–30 ka) which are dominated by detrital (titano‐)magnetite particles, the studied relict magnetic mineral samples exhibit a similar behavior in recording the depositional remanent magnetization. Furthermore, the obtained paleosecular variations spanning the past 8 ka reproduce the high intensity patterns observed in the regional archeomagnetic and volcanic datasets. Thus, the successful reconstruction of paleomagnetic secular variations from the anoxic Black Sea sediments greatly extend the application of paleomagnetism in sediments deposited in water with a reducing sub‐surface environments from where paleomagnetic data are generally sparse. Plain Language Summary: The Earth's magnetic field can be recorded by magnetic minerals during their deposition within a water column, and are later preserved in sediments. The geomagnetic field signal may be biased if the magnetic minerals are subsequently altered because of changes in bottom water redox conditions. However, relict magnetic minerals are resistant to ambient environmental changes and thus have great potentials to record reliable paleomagnetic signals. To attest this novel idea, we systematically investigated sediments form the Black Sea under strong anoxic bottom water conditions. Our results demonstrate that the relict magnetic minerals survived in the Black Sea sediments covering the past eight thousand years. By comparison with detrital (titano‐)magnetite samples, we found that relict magnetic mineral samples have similar behavior in recording the geomagnetic field. Moreover, the geomagnetic field variations reconstructed from the Black Sea sediments are comparable with other validated regional datasets for the past eight thousand years. Therefore, our new study significantly extends the application of paleomagnetic methods in a wider range of sedimentary redox conditions. Key Points: Relict minerals of hemoilmenite, Fe‐Mn and Fe‐Cr spinels, and magnetic inclusions are magnetic carriers in studied Black Sea sediments The ability in recording the DRM by relict magnetic minerals are comparable with detrital (titano‐)magnetite The obtained paleosecular variations resemble reginal field patterns observed in archeomagnetic and volcanic datasets for the past 8 ka